Pelaksanaan Penyerahan Protokol Notaris yang Meninggal Dunia Kepada Majelis Pengawas Daerah Berdasarkan Undang-Undang Tentang Jabatan Notaris Studi Kasus di Kabupaten Padang Pariaman - Ihsan, Junaldi; Fendri, Azmi; Delfiyanti, Delfiyanti (UNES Law Review, 2023)
For this reason, this research aims to explain: 1. How is the implementation of the handing over of protocols for notaries who have died in Padang Pariaman District? In this writing, empirical juridical legal research (sociolegal research) is used. The Juridical Approach is used to analyze various Legislative Regulations related to the above problems. In contrast, the Empirical Approach is used to analyze law by looking at legal realities in society. The implementation of the submission of the notary protocol begins with notification of the death of a notary by the heirs to the Padang Pariaman Regency MPD. Then the MPD appoints a notary recipient of the protocol to forward it to the Minister of Law and Human Rights of the Republic of Indonesia to issue a ministerial decision as a basis for the legality of the protocol holder.